Adherence and side effects of three ferrous sulfate treatment regimens on anemic pregnant women in clinical trials Adesão e efeitos colaterais em ensaio clínico comparando três esquemas de tratamento com sulfato ferroso em gestantes anêmicas - Ariani Impieri de Souza; Malaquias Batista Filho; Cristiane Campello Bresani; Luiz Oscar Cardoso Ferreira; José Natal Figueiroa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The objective of this study was to analyze adherence and side effects of three iron supplement regimens (ferrous sulfate) on anemic pregnant women. The clinical trial involved 150 women between the 16th and 20th gestational weeks, at low obstetric risk and with hemoglobin concentration of between 8.0 and 11.0g/dL. Treatment was provided by ferrous sulfate with 60mg of elemental iron during 16 (± 1) weeks, in three regimens: single tablet a week (n = 48); single tablet twice a week (n = 53) or single tablet a day (n = 49). The outcomes were adherence, assessed through interviews and by counting tablets, and side effects, according to patient information. The adherence showed a declining trend (92%, 83% and 71%; p = 0.010) and the side effects revealed a growing trend (40%, 45% and 71%; p = 0.002) as the dosage increased. Diarrhea and epigastric pain were significantly associated with the dose administered (p = 0.002). These results suggest that in anemic pregnant women, complaints are directly proportional and the compliance is inversely proportional to the amount of medicinal iron. O objetivo deste estudo foi analisar a adesão e os efeitos colaterais de três esquemas de suplementação com sulfato ferroso em gestantes anêmicas. O ensaio clínico incluiu 150 mulheres entre a 16ª e 20ª semanas de gestação, de baixo risco obstétrico e com concentração de hemoglobina entre 8,0 e 11,0g/dL. A intervenção foi realizada com 60mg de ferro elementar, durante 16 (±1) semanas, em três esquemas: uma drágea semanal (n = 48); uma drágea duas vezes por semana (n = 53) ou uma drágea diariamente (n = 49). Os desfechos foram adesão, verificada por entrevista e contagem das drágeas, e efeitos colaterais auto-relatados pelas pacientes. A adesão apresentou tendência declinante (92%, 83% e 71%; p = 0,010) e os efeitos colaterais, ascendente (40%, 45% e 71%; p = 0,002) com o aumento da dose prescrita. Diarréia e dor epigástrica estiveram significativamente associadas à dose administrada (p = 0,002). Os resultados sugerem que em gestantes anêmicas as queixas e a adesão ao tratamento com sulfato ferroso são, respectivamente, direta e inversamente proporcionais à quantidade do ferro medicamentoso.